Evaluation of Systemic C-reactive Protein as a Systemic Inflammatory Marker in the Blood for Patients Undergoing Minor Oral Surgical Procedures - Mustafa M. Abdulla Alyassin; Sahar Shakir Al-Adili (College of Dentistry/ University of Baghdad, 2016)
Background: C-reactive protein (CRP) is an acute phase protein that its plasma levels increase after trauma or surgery so it is used as an indicator for the level of inflammation after surgery. The objective of this study is to investigate pre- and post-operative levels of CRP in three types of oral surgical interventions (Apicoectomy, Impaction, and Impacted teeth exposure). Materials and Methods: A total number of (48) healthy individuals aged (20-60) years who needed oral surgical intervention for either (removal of impacted third molars, exposure of an impacted canine, or Apicoectomy). A 4ml venous blood was obtained from each patient at two occasions (pre-operatively at the day of operation and post-operatively after 48 hours), then centrifuged for 15 minutes at (1000x g) and finally the sera were separated and stored at (-20º C) to be used for later analysis by Enzyme Linked Immuno Sorbent Assay (ELISA). Results: There was statistically high significant increase in the level of CRP after oral surgical interventions in all types of operations (the CRP mean value pre-operatively was 2.407925 mg/L, post-operatively after 48hr was 8.486725 mg/L, and the P-value was 0.000). Also there was a high significant difference between apicectomy, impaction, and exposure operations in the level of CRP at day two postoperatively (P-value was 0.000). Conclusion: An inflammatory process develops after oral surgical interventions which necessitate the use of anti-inflammatory agents after these procedures and that the severity of inflammation measured by means of CRP levels is correlated to the degree of swelling, length, and type of the surgical procedure